Can doctors improve the patient experience by rearranging the furniture and equipment in their office? A video recorded simulation - Moyez Jiwa; Catherine Krejany; Lee Gaedtke; Epi Kanjo; Ruthra Nagendran; Carolyn O'Shea; Iain Greenlees (Patient Experience Journal, 2019)
The design of this study is a video-recorded simulated consultation. Its aim is to evaluate the effect of changing seating arrangements and stethoscope visibility on patient enablement and non-verbal behaviour. Twelve simulated consultations with six actor-patients and a ‘real’ doctor were video recorded. Either the ‘real’ doctor or actor-patient, blind to the hypothesis sat in large executive office chair during the consult. The patient entered the room afresh for each consult. Consultation quality and outcomes were independently evaluated on three measures: The Patient Enablement Index (PEI), the Leicester Assessment Package (LAP); Non-Verbal Communication (NVC). Both expert reviewers were also blind to the study aim. The results: the doctor’s performance was consistent on the LAP score (P > 0.05). There was a significant improvement in patient enablement (p=0.03) and non-verbal communication (p=0.003) when the actor-patients occupied the executive chair. The visibility of the stethoscope did not have a measurable effect on these measures. There was evidence that when patients occupy the larger chair in the consulting room there is significant objective improvement in the measures of patient experience of the meeting.